Stocks and fluxes of carbon associated with land use change in Southeast Asian tropical peatlands: a review - Hergoualc'h, Kristell; Verchot, Louis V. (2011)
The increasing and alarming trend of degradation and deforestation of tropical peat swamp forests may contribute greatly to climate change. Estimates of carbon (C) losses associated with land use change in tropical peatlands are needed. To assess these losses we examined C stocks and peat C fluxes in virgin peat swamp forests and tropical peatlands affected by six common types of land use. Phytomass C loss from the conversion of virgin peat swamp forest to logged forest, fire-damaged forest, mixed croplands and shrublands, rice field, oil palm plantation, and Acacia plantation were calculated using the stock difference method and estimated at 116.9 ± 39.8, 151.6 ± 36.0, 204.1 ± 28.6, 214.9 ± 28.4, 188.1 ± 29.8, and 191.7 ± 28.5 Mg C ha-1, respectively. Total C loss from uncontrolled fires ranged from 289.5 ± 68.1 Mg C ha-1 in rice fields to 436.2 ± 77.0 Mg C ha-1 in virgin peat swamp forest. We assessed the effects of land use change on C stocks in the peat by looking at how the change in vegetation cover altered the main C inputs (litterfall and root mortality) and outputs (heterotrophic respiration, CH4 flux, fires, and soluble and physical removal) before and after conversion. The difference between the soil input-output balances in the virgin peat swamp forest and in the oil palm plantation gave an estimate of peat C loss of 10.8 ± 3.5 Mg C ha-1 yr-1. Peat C loss from other land use conversions could not be assessed due to lack of data, principally on soil heterotrophic respiration rates. Over 25 years, the conversion of tropical virgin peat swamp forest into oil palm plantation represents a total C loss from both biomass and peat of 427.2 ± 90.7 Mg C ha-1 or 17.1 ± 3.6 Mg C ha-1 yr-1. In all situations, peat C loss contributed more than 63% to total C loss, demonstrating the urgent need in terms of the atmospheric greenhouse gas burden to protect tropical virgin peat swamp forests from land use change and fires.